DRUG INDUCED NEUROPATHY - Anisa Syahfitri Hanum; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2023)
Neuropathy is a painful condition and originates from a variety of etiologies. Many drugs can cause neuropathy, which is known as Drug-Induced Neuropathy (DIN), which is included in iatrogenic cases. These drugs are chemotherapy agents, antimicrobials, cardiovascular drugs, psychotropics, anticonvulsants, etc. Not all neuropathies require pharmacological therapy, but simply stop therapy, and the complaints will improve (reversible). However, there are quite a few DINs with a “coasting" response neuropathy when DIN is stopped. This review synthesizes current clinical concepts regarding mechanisms, drug-induced neuropathy, and treatment options for drug-induced peripheral neuropathy.